The Effect of Auditor Independence, Good Corporate Governance, and Audit Quality on the Integrity of Financial Reporting (Case Study of Banking Sector Companies Listed on the Indonesia Stock Exchange in 2019-2023) - Daniel Efrian Kristianto; Sari Andayani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The era of globalization has had a significant impact on the world of finance and banking. However, this also challenges companies, including improving the integrity of the financial statements. The Indonesia Stock Exchange (IDX) issued a financial statement integrity in 2020-2023 regarding the inconsistency of several banks in presenting their financial statements. The institution most adversely affected by fraud is the financial and banking industry at 41.4%. This loss is caused by investor distrust which makes companies in this sector lose money due to fraudulent financial statements. Based on this phenomenon, financial reporting is required to be disclosed with integrity. Many factors can affect the integrity of financial statements such as auditor independence, good corporate governance, and also the quality of the audit performed by the company. This study aims to examine the effect of auditor independence, independent commissioners, managerial ownership, institutional ownership, audit committees, and quality of audits on the integrity of financial reporting. The object studied was banking sector companies listed on the IDX in 2019-2023 with a sample of 115. The research method used was multiple linear regression analysis to identify the relationship between the independent variables on the dependent variable.